2021
DOI: 10.3389/fmed.2021.732528
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk Between SMPDL3b and NADPH Oxidases Mediates Radiation-Induced Damage of Renal Podocytes

Abstract: Patients undergoing radiotherapy (RT) for various tumors localized in the abdomen or pelvis often suffer from radiation nephrotoxicity as collateral damage. Renal podocytes are vulnerable targets for ionizing radiation and contribute to radiation-induced nephropathies. Our prior work previously highlighted the importance of the lipid-modifying enzyme sphingomyelinase acid phosphodiesterase like 3b (SMPDL3b) in modulating the radiation response in podocytes and glomerular endothelial cells. Hereby, we investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
(77 reference statements)
0
6
0
Order By: Relevance
“…Our group previously demonstrated that IR‐induced loss of SMPDL3b triggers podocytes dysfunction by disrupting their cytoskeletal integrity and sphingolipid homeostasis. However, SMPDL3b overexpression conferred radioresistance by partially reversing these alterations, enhancing DSBs repair, 32 and mitigating oxidative stress by decreasing the activity and protein expression of NADPH oxidases 41 . Furthermore, we reported that SMPDL3b modulates IR‐induced damage of human glomerular endothelial cells, whereby it gets upregulated post‐IR in contrast to podocytes 38 .…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Our group previously demonstrated that IR‐induced loss of SMPDL3b triggers podocytes dysfunction by disrupting their cytoskeletal integrity and sphingolipid homeostasis. However, SMPDL3b overexpression conferred radioresistance by partially reversing these alterations, enhancing DSBs repair, 32 and mitigating oxidative stress by decreasing the activity and protein expression of NADPH oxidases 41 . Furthermore, we reported that SMPDL3b modulates IR‐induced damage of human glomerular endothelial cells, whereby it gets upregulated post‐IR in contrast to podocytes 38 .…”
Section: Discussionmentioning
confidence: 85%
“…However, SMPDL3b overexpression conferred radioresistance by partially reversing these alterations, enhancing DSBs repair, 32 and mitigating oxidative stress by decreasing the activity and protein expression of NADPH oxidases. 41 Furthermore, we reported that SMPDL3b modulates IR-induced damage of human glomerular endothelial cells, whereby it gets upregulated post-IR in contrast to podocytes. 38 Therefore, our work hints that SMPDL3b changes are cell-specific.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…After 1 week of acclimation, mice were used as control mice or subjected to modeling as RKI mice. RKI mice were irradiated with X-rays at a dose of 14 Gy, with a dose rate of 2.35 cGy/min at the kidney site, 5 days per week for 4 weeks (180 times of rotation during each irradiation to optimize dose uniformity) [ 28 , 29 ]. After 4 weeks, a fully automated biochemical analyzer (AU5800, Beckman Coulter Inc., Chaska, MN) was used to measure serum blood urea nitrogen (BUN) and creatinine values.…”
Section: Methodsmentioning
confidence: 99%
“…In brief, the sections were stained with hematoxylin for 10 min, differentiated with 1% hydrochloric acid alcohol for 30 s, stained with eosin for 1 min, and dehydrated with gradient alcohol (concentrations of 70%, 80%, 90%, 95%, and 100%, respectively) for 1 min each. After being cleared with xylene, the sections were sealed with neutral gum, and the morphological changes were finally photographed and observed under a light microscope (BX50; Olympus Corp., Tokyo, Japan) [ 29 ].…”
Section: Methodsmentioning
confidence: 99%